From theory to practice: challenges and rewards of implementing ketogenic metabolic therapy in mental health - Laurent, Nicole (Frontiers in Nutrition, 2024)
This perspective article delves into the implementation of Ketogenic Metabolic Therapy (KMT) by a mental health counselor who attempts to bridge the gap between emerging research and real-world clinical application. Grounded in the author's clinical experiences, the article communicates the potential of KMT in mental health care, highlighting both its therapeutic promise and the insights gained from hands-on patient interactions. While the adoption of KMT necessitates adjustments in societal, emotional, and dietary domains, especially within diverse mental health contexts, these challenges are surmountable with appropriate guidance and support. The article encourages the capture of qualitative data alongside quantitative measures and advocates for an approach that considers the broader implications of improved mental wellbeing on families and communities. As the field advances, interdisciplinary collaborations between researchers and clinicians will be pivotal in refining and expanding the application of KMT, ultimately enhancing patient outcomes and elevating the standard of mental health care.